Effects of Meniran (Phyllanthus niiuii L.) Herbs-Hexane Extracts Against the Toxic Effect of Aflatoxin Br in The Liver of Rattus norvegicus Rats - Wiryatun Lestariana, Wiryatun Lestariana (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1997)
The principal objective of this study is to provide more extensive description of the chemopreventive effect of rneniran herbs-hexan extracts against the toxic effect of aflatoxin B1 in the liver of Rattus norvegicus rats. The subjects consisted of sixteen male rats Rattus norvegicus in good general condition, 1 - 2 month old, with body weight around 62 - 68.5 grams, divided into 4 groups of four rats each. Water and ad libid were given to All of the groups of the rats. The first group was given 1 ml of emulsion of coconut oil. The second group was given 30 mg of meniran herbs-hexane extracts in 1 ml emulsion. The third group was given 15 g aflatoxin B, (AFB,) in 1 ml emulsion. The fourth group was given 30 mg of meniran herbs-hexane extracts and 15 g of AFB, in 1 ml of emulsion. Extract and AFBi were given orally by an aplicator for 16 weeks. By analysis of variance the results showed that the effect of meniran herbs-hexane extracts against the toxic effect of aflatoxin B1 demonstrated a significant effect (p < 0,01) in serum alanine aminotransferase (glutamic pyruvictransaminase). Aflatoxin B, increased serum alanine aminotransferase significantly (p < 0.001) in comparison with control (the group of rats treated with 1 ml emulsion and the group of the rats treated with 30 mg extracts). Histological feature in the group of rats treated with AFBi showed bad liver features compared to the other groups. There were altered foci in the hepatocytes (3/5) and the bile duct epithelial cells demonstrated hyperplasia as well as metaplasia (5/5). The group of the rats treated with meniran herbs-hexane extracts and AFB, showed normal hepatocytes and some of bile duct epithelial cells showed proliferation. The other groups of the rats respectively treated with coconut oil emulsion and meniran herbs-hexane extracts showed normal hepatocytes and bile ducts epithelial cells. It is concluded that meniran herbs-hexane extracts could be used to reduce aflatoxin B, toxicity in the rat liver.Keywords: Phyllanthus niruri L. herbs-hexane extracts - aflatoxin Bt - serum alanine aminotransferase - bileduct epithelial cells - hepatocytes - Rattus norvegicus